Droplet Spectrum from CP Nozzles Affected by Pressure, Flat-Fan, and Deflection Angles in Aerial Applications of Glyphosate - Alves, Guilherme Sousa; Vieira, Bruno C.; Carvalho, Fernando K.; Cunha, Joao Paulo A. R. da; Antuniassi, Ulisses R. [UNESP]; Kruger, Greg R.; Linscott, D. J. (Astm International, 2019)
Spray classification based on droplet size has been used worldwide to characterize nozzles in relation to efficacy and drift potential. The objectives of this study were to evaluate the effect of pressure, flat angle of nozzle, and deflection angle on droplet spectrum in aerial applications of glyphosate using a high-speed wind tunnel. Two independent studies were conducted: one evaluating pressure (207, 310, 414 kPa) and deflection angle (0 degrees, 30 degrees, 60 degrees, 90 degrees) with CP-11TT 8008 nozzles, and another study evaluating flat-fan angle (20 degrees, 40 degrees, 80 degrees) of CP-11TT nozzles with 08 orifice size and the same deflection angles used in a previous study, at 207 kPa pressure. The solution was prepared with water and Roundup PowerMax at 2.34 L ha(-1) as a source of glyphosate, simulating a carrier volume of 30 L ha(-1). Droplet size data were recorded in a high-speed wind tunnel using a Sympatec HELOS laser diffraction system. The droplet size was affected by interactions between pressure versus deflection angle and flat-fan versus deflection angle. Selecting narrower angles of flat-fan nozzles and deflections, as well as higher pressures, are viable alternatives to mitigate glyphosate drift from aerial applications.
Keywords: herbicide; spray droplet size; potential risk of drift; high-speed wind tunnel